Immunomodulatory Effects of Newcastle Disease Virus Strain AF2240 on Human Peripheral Blood Mononuclear Cells Activation and Cytolytic Activity - Lam, Han Yuen (2011)
Immunomodulator agent is a substance that can regulate the human immune system to reach therapeutic goal. In this study, Newcastle disease virus (NDV) was used as the immunomodulator to alter human immunity in order to replace current cancer therapies that cause severe side effects to cancer patients. The aim of this study is to examine the in vitro immunomodulatory effects of NDV strain AF2240 on human peripheral blood mononuclear cells (PBMC) proliferation, cytokines production and cytolytic effect on tumor cells. The cell proliferation of NDV-treated PBMC was determined by BrdU cell proliferation assay. NDV virus titer 2 HAU was able to induce cell proliferation up to 30% indicating that low virus titer was sufficient to stimulate the human immune system. From the immunophenotyping results, the percentage of CD56 cells and cells expressed activating receptors (CD16 and NKG2D), which are normally expressed by natural killer (NK) cells, were increased. Therefore, NK cells might be the predominant activated effector cells in human PBMC. In addition, production of cytokines also revealed activation degree of PBMC, upon virus induction. After virus treatment for 72 hours, the level of cytokines, like IFN-γ, IL-2 and IL-12 were increased. These cytokines functioned to cause cell activation and proliferation and further augment the immune activities. In addition, the cytolytic effect on human tumor cells was determined by co-culturing NDV activated PBMC and tumor target cells. Results showed the activated human PBMC caused cytotoxicity towards human breast cancer, MCF-7 cells, by inducing apoptosis. Also, activated PBMC was cytotoxic on human liver cancer, HepG2 cells, and human leukemic, K562 cells. The findings showed that expression of perforin and granzyme B involved in cytolytic effect of activated PBMC on human tumor cells. In conclusion, NDV strain AF2240 was indicated as a potent immunomodulator to activate human PBMC that leads to cell proliferation, cytokines synthesis and enhancement of cytolytic effect on tumor cells.